The impact of the Asignación Universal por Hijo Program on educational outcomes and student tasks in Argentina - Monserrat Serio; Martina Herrera (Arizona State University, 2021)
This paper explores the effect of the principal conditional cash transfer program known as Asignación Universal por Hijo (AUH) of Argentina on educational outcomes such as attendance, performance in reading and mathematics, and grade repetition. Also, we analyze the impact on non-school tasks that students performed which can replace the time dedicated to studying and permanence in the school. We use the Aprender 2016 assessment database focusing on data of students from primary and high school. We use non-experimental data exploiting the question about if the student's family is a beneficiary of the AUH. We perform a Coarsened Exact Matching (CEM) and estimate the average treatment effect on the treated of the program. The results show that the AUH had a positive impact on attendance augmenting the probability of not being absent from class fewer than eight and seventeen days in 1.3 p.p and 1 p.p., respectively. However, positive effects on educational performance and conducting of non-school tasks are not found. We also found heterogeneous effects, for male students the program increases the probability of missing fewer classes at all levels between 0.4 p.p. and 1.5 p.p. and students from rural areas and public schools have reassigned non-school tasks.